2015
DOI: 10.1085/jgp.201511377
|View full text |Cite
|
Sign up to set email alerts
|

Ruling out pyridine dinucleotides as true TRPM2 channel activators reveals novel direct agonist ADP-ribose-2′-phosphate

Abstract: ADP-ribose-2′-phosphate acts as a direct agonist of TRPM2, whereas NAD, NAAD, and NAADP do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 34 publications
(112 reference statements)
5
57
0
Order By: Relevance
“…Oxidative stress, TNF␣, and amyloid ␤-peptide are among the key extracellular signals known to activate TRPM2 (10 -13). Stimulation with these extracellular signals results in production of adenosine diphosphate-ribose (ADPR), which activates the channel by binding to the TRPM2 C-terminal NUDT9-H domain (7,(13)(14)(15)(16)(17)(18)(19). A rise in intracellular Ca 2ϩ and calmodulin also positively regulate TRPM2 (20 -22), and acidification can inhibit channel activity (23)(24)(25).…”
Section: Transient Receptor Potential (Trp)mentioning
confidence: 99%
“…Oxidative stress, TNF␣, and amyloid ␤-peptide are among the key extracellular signals known to activate TRPM2 (10 -13). Stimulation with these extracellular signals results in production of adenosine diphosphate-ribose (ADPR), which activates the channel by binding to the TRPM2 C-terminal NUDT9-H domain (7,(13)(14)(15)(16)(17)(18)(19). A rise in intracellular Ca 2ϩ and calmodulin also positively regulate TRPM2 (20 -22), and acidification can inhibit channel activity (23)(24)(25).…”
Section: Transient Receptor Potential (Trp)mentioning
confidence: 99%
“…Importantly, these activating signals are linked to the cellular redox state (Heiner et al, 2003). Other studies have also indicated that NAD or H 2 O 2 may not activate TRPM2 directly (Buelow et al, 2008; Perraud et al, 2005; Toth and Csanady, 2010; Toth et al, 2015). Here, we addressed the role of the ROS-sensing function of TRPM2 in regulating neutrophil migration.…”
Section: Introductionmentioning
confidence: 99%
“…TRPM2 is a Ca 2+ -permeable channel gated by ADPR, ADPR-2′-phosphate (ADPRP), and Ca 2+ (Toth et al, 2015). In addition to acting as a channel on the plasma membrane, TRPM2 is also functional as a lysosomal channel in pancreatic β-cells and dendritic cells.…”
Section: Lysosomal Calcium Homeostasismentioning
confidence: 99%